El universalismo científico del Barón Ignaz von Born y la transferencia de tecnología minera entre Hispanoamérica y Alemania a finales del siglo XVIII - Hausberger, Bernd (El Colegio de México, A.C., 2009)
During the last quarter of the eighteenth century, the Borbonic Crown sought to increase mining yields in Spanish America by means of technological modernization: transferring from Central Europe the amalgamation technique described  by Ignaz von Born, with disappointing results. This work seeks to show how an economic project may fail due largely to underlying political and scientific ideas and prejudices inscribed within the discourses, values, and culture of the time, which prevented  the actors from understanding the problem they sought to resolve. Thus, faith in the eventual  triumph of reason,  discovered  in the eighteenth century but limited to Europe, guided the project's leaders in bringing that technology back to Spanish America.